Threshold temperatures for seed germination in nine species of Verbascum (Scrophulariaceae). Issue 1 (8th December 2015) - Catara, Stefania; Cristaudo, Antonia; Gualtieri, Andrea; Galesi, Rosario; Impelluso, Carmen; Onofri, Andrea
Abstract: Light and fluctuating temperatures are two important factors triggering seed germination. The aim of this work was to: (1) elucidate the effect of temperature, light regime and storage time on seed germination in nine taxa of Verbascum spp., collected from different habitats in the Mediterranean area; and (2) estimate threshold temperatures for seed germination. For all taxa, germination assays were performed at constant and fluctuating temperatures, both in continuous darkness (D) and in alternating light/dark (L/D; 12 h photoperiod). Final germinated proportions (FGPs), base ( T b ), optimal ( T o ) and cut-off ( T c ) temperatures were derived. At constant temperatures, seed germination was strongly suppressed under the D regime. In L/D, the effect of storage time was very small and the highest FGPs were observed from 15 to 30°C (40–100%), depending on the species. T b ranged from below 7 to above 10°C and it appeared to be constant within each seed lot. T o and T c showed some within-lot variability and were higher for fast-germinating seeds in each lot. Considering fluctuating temperatures, germination appeared to be quicker and more complete than at constant temperatures. The germination of Verbascum spp. is favoured in L/D and fluctuating temperatures, which explains their pioneer character when positioned near the soil surface and under a low vegetation canopy. V. arcturus and V. pinnatifidum were shown to be less favoured by L and fluctuating temperatures, which might explain their ability to germinate in rocky areas or sandy dunes, even when they are not directly exposed to the light.